The effect of profitability ratio on stock prices at registered food and beverage companies on the indonesian stock exchange (BEI) in 2020-2022 - Mulianata, Lisa; Fahrianta, Riswan Yudhi; Syahdan, Saifhul Anuar (Enrichment : Journal of Management, 2024)
This research aims to analyze the effect of profitability ratios on stock prices in food and beverage companies listed on the Indonesian Stock Exchange in 2020-2022. Research variables for profitability include Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS) and Net Profit Margin (NPM). The sample consists of 15 companies with 45 observation data selected using the purposive sampling method. Multiple regression analysis with SPSS was used to process the data. Data comes from annual financial reports of food and beverage companies on the IDX. The research results show that ROA and NPM do not have a significant effect on stock prices. ROE and EPS have a significant effect on stock prices